(untitled) (Gestão & Regionalidade, 2015)
The aim of this study was to analyze the Orla Marítima de João Pessoa (PB) [João Pessoa Waterfront] as an organization resulting from its daily practices and its Management Committee (Waterfront Project of the Federal Government). It is understood as an organization a collective and dynamic process around a practice that allows its recognition and social maintenance, considering the socio-material relations. The collection of empirical data used an ethnomethodological approach and was performed in two stages, the first through participation in twelve meetings of the Comitê Gestor Orla [Waterfront Management Committee], and the second with immersion in the Waterfront itself. Among the results, it was pointed out that the organizing occurs through scientific, economic, political, third sector, and tourism/leisure sociomaterial practices. It was found that the use of the Waterfront goes beyond what is discussed in its management committee and, as a social organization, it is only possible because there is sociomaterial interaction.